KINERJA GURU DALAM PEMBELAJARAN PADA SMPIT X BERDASARKAN METODE LOGIKA FUZZY - Agustina, Merry (Universitas Bina Darma, 2017)
Schools, teachers and learning are interrelated components. School as a forum that organizes learning for students, and teachers as professionals who transfer knowledge. Performance is a universal concept that is the operational effectiveness of an organization, organization, and employees based on predefined standards and criteria. The performance of teachers can be defined as the extent to which a teacher works maximally in accordance with the ability he has in an effort to achieve institutional goals. This study aims to determine the performance of SMPIT